On Liberty - Mill, John Stuart 1806-1873; Edited with an introduction by Gertrude Himmelfarb (New Zeland Penguin Books, 1976)
The writings of John Stuart Mill have become the cornerstone of political liberalism. He defines the nature of civil liberty, and most importantly, the harm principle. In order to preserve the liberties included in the concept of Civil Liberty, the author points out there must be limits to the action of the Government.
"First published 1859.
Keywords: Liberty -- Liberté -- Vrijheid